Complications of Chronic Suppurative Otitis Media - ., Arifullah; Hasan, Syed Zafar; Gul, Islam; Din, Waqar -Ud-; Ahmad, Aftab (Journal of Gandhara Medical and Dental Science, 2016)
OBJECTIVE The aim of the study was to find the complications of chronic suppurative otitis media. MATERIAL AND METHODS The study was descriptive study conducted from 1st January 2008 to 31 December 2010 (3 years duration) at ENT department Khyber Teaching Hospital Peshawar. Total 250 patients of all age having complications due to chronic suppurative otitis media enrolled from admitted patients in ENT department Khyber Teaching Hospital Peshawar were included in the study, using convenience (non-probability) sampling. RESULTS In total of 250 patients, all (100%) were having history of discharging ear, decreased hearing 250 (100%), earache in 75 (30%), fever in 31(12.4%), headache in 28 (11.2%), nausea and vomiting in 23 (9.2%) patients. The extracranial complications were found in 204/250 (81.6%) patients with mastoiditis being the most common in 155/204 (75.98%) patients followed by sensory reural hearing loss, post auricular abscess, facial paralysis, petrositis, labynthitis, Bezold’s abscess and cetili’s abscess in 7.84%, 6.37%, 5.88%, 1.7%, 0.98%, 0.98% and 0.49% patients respectively. While the intracranial complications were found in 46/250 (18.4%) patients with meningitis being the most common in 28/46 (60.9%) followed by brain abscess in 26%, lateral sinus thrombosis in 8.7% and otitic hydrocephalus in 4.4% patients. CONCLUSION Early detection and treatment of complications as a result of chronic suppurative otitis is vital to prevent morbidity and mortality.